2006
DOI: 10.1016/j.seizure.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results with vagus nerve stimulation in children with pharmacoresistant epilepsy

Abstract: In this series VNS was well-tolerated and effective as add-on therapy for refractory seizures in children of all ages. Response was even more favorable in the younger group (<12 years at implantation). Infection and lack of efficacy were the most common reasons for discontinuation of long-term VNS therapy in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 33 publications
11
112
0
12
Order By: Relevance
“…Typically, these symptoms abate with time or alteration of the stimulation parameters. 2,3,19,36,44,50 Significant or permanent injuries to the vagus nerve or development of dysphagia following implantation were rare (< 0.5%) in our series, and the rate is comparable to rates reported for other series (≤ 4%). The rate of infection was under 3%, which is comparable to rates reported in most large series (0%-8%) and similar to those reported for other implantable devices.…”
Section: Complications and Cosmetic Considerationssupporting
confidence: 86%
“…Typically, these symptoms abate with time or alteration of the stimulation parameters. 2,3,19,36,44,50 Significant or permanent injuries to the vagus nerve or development of dysphagia following implantation were rare (< 0.5%) in our series, and the rate is comparable to rates reported for other series (≤ 4%). The rate of infection was under 3%, which is comparable to rates reported in most large series (0%-8%) and similar to those reported for other implantable devices.…”
Section: Complications and Cosmetic Considerationssupporting
confidence: 86%
“…Indeed, younger patients implanted before the age of 12 years appeared to respond better than the older group of pediatric patients. 57 Notably, five of six children with Lennox-Gastaut syndrome had a 90% reduction of seizures at 30 months of follow-up. Other studies have demonstrated similar favorable responses of seizures associated with Lennox-Gastaut to VNS.…”
Section: Vns For Refractory Seizures In the Pediatric Populationmentioning
confidence: 92%
“…34,56 Longterm follow-up at 36 months revealed a mean seizure frequency reduction of 74%. 57 Strong associations between improved seizure severity and QOL have been made, as has been seen in the adult population. 34,58 In fact, Յ80% of patients had an improvement in the parental conception of the child's QOL.…”
Section: Vns For Refractory Seizures In the Pediatric Populationmentioning
confidence: 94%
“…38,63 Long-term, follow-up at 36 months revealed a mean seizure frequency reduction of 74%. 64 VNS does appear to be a potential option for children under the age of Food and Drug Administration-approved indications. A recent report of VNS in children less than 5 years old demonstrated that 83% of patients had a significant decrease in seizure frequency at 22 months of follow-up.…”
Section: Vns For Refractory Seizures In the Pediatric Populationmentioning
confidence: 99%
“…Indeed, younger patients implanted before the age of 12 years appeared to respond better than the older group of pediatric patients. 64 Notably, children with Lennox-Gastaut syndrome have been shown to respond very favorably to VNS 66,67 The efficacy of VNS appears to compare favorably to corpus callosotomy in these patients. 68 Other studies have demonstrated similar seizure reduction in tuberous sclerosis complex.…”
Section: Vns For Refractory Seizures In the Pediatric Populationmentioning
confidence: 99%